Recommended Features of Learning Management System Using Feature-Oriented Method Software Development on Moodle - Hari Windu Asrini; Galih Wasis Wicaksono; Budiono Budiono; Gilang Ramadhan; Evi Dwi Wahyuni (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2021)
Learning Management System (LMS) serves as a learning media effective for online learning during Covid-19. The rising use of LMS these days indicates that LMS features need to be further measured for their relevance to the National Standards of Higher Education (SN-Dikti). This measurement is also essential to be applied for five blended learning criteria for flexible time and place to access lessons. The objective of this research is to analyze the features of the LMS implemented on Moodle version 3.10. The analysis of the features was carried out by employing the methods of Feature-Oriented Software Development (FOSD), a method that elaborates software system relating to existing features of LMS, involving: 1) Canvas; 2) Edmodo; 3) Google Classroom; 4) Moodle; 5) Zoom Meeting; 6) Google Meet; 7) efront, and 8) Microsoft Teams. In accord with the testing and validation by experts, the research revealed that there were 56 features of LMS pertinent to learning and assessment standards of SN-Dikti and E-learning self-study criteria with other blended-media or events, instructor-led program, live e-learning, on the job training, simulation, and lab centered on blended learning. Those 56 features were approved by experts and implemented by employing Moodle version 3.10 relevant to the SN-Dikti and blended learning